2012
DOI: 10.4103/0974-2727.98669
|View full text |Cite
|
Sign up to set email alerts
|

Closed Pleural Biopsy is Still Useful in the Evaluation of Malignant Pleural Effusion

Abstract: Background:Pleural fluid cytology for malignant cells is the easiest way to diagnose malignant pleural effusion with good sensitivity and specificity. With the introduction of medical thoracoscopy, the use of closed pleural biopsy for the diagnosis of cytology negative malignant pleural effusion is gradually decreasing. However use of thoracoscopy is limited due to its high cost and procedure related complications.Aims:The aim was to assess the usefulness of closed pleural biopsy in the diagnosis of malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Yield of fluid cytology also depends on the underlying primary tumour, sample preparation and experience of the cytologist. (11) In the current study pleural fluid cytology was positive in 62% cases, which is similar to the previous observations. In cases where pleural metastasis occurs, there is tumour cell seeding of the mesothelial surface of pleura.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Yield of fluid cytology also depends on the underlying primary tumour, sample preparation and experience of the cytologist. (11) In the current study pleural fluid cytology was positive in 62% cases, which is similar to the previous observations. In cases where pleural metastasis occurs, there is tumour cell seeding of the mesothelial surface of pleura.…”
Section: Discussionsupporting
confidence: 92%
“…This was comparable to what has been published earlier by Bhattacharya et al, which also showed a 54% adenocarcinoma diagnosis among cytology positive malignant effusions. (11) Zay Soe et al in their study reported a positivity in pleural fluid cytology of 64.4%. However, the commonest diagnosis for them was metastatic large cell carcinoma.…”
Section: Discussionmentioning
confidence: 87%
“…Edmondstone et al (32) and McLean et al (33) reported slightly lower diagnostic sensitivities of 60% and 62%, respectively. On the other hand, in another four series, the sensitivity varied between 43.8% and 48.5% (3,10,34,35). These data are important is assessing the improvement in the diagnostic sensitivity of the cytology that BCPB provides, which was 15% in our series, and would have avoided one pleuroscopy for every seven BCPB that were performed -figures slightly lower than those obtained in a review on this topic (an improvement of 19.4%, and the need for 5.2 BCPB to avoid one pleuroscopy) (36).…”
Section: Discussionmentioning
confidence: 88%
“…Closed pleural biopsy was positive for malignancy in cases where pleural fluid cytology was negative. Chang and associates [33] performed thoracocentesis, closed pleural biopsy and bronchoscopy in 140 patients with pleural effusions. The combination of these procedures resulted in diagnosis in 100 (71%) of the patients: 68 patients were diagnosed by thoracocentesis or pleural biopsy or both; bronchoscopy provided diagnosis in additional 32 patients.…”
Section: Discussionmentioning
confidence: 99%